2010
DOI: 10.1088/0004-6256/139/6/2300
|View full text |Cite
|
Sign up to set email alerts
|

Light Curves and Period Changes of Type Ii Cepheids in the Globular Clusters M3 and M5

Abstract: Light curves in the B, V , and I c passbands have been obtained for the type II Cepheids V154 in M3 and V42 and V84 in M5. Alternating cycle behavior, similar to that seen among RV Tauri variables, is confirmed for V84. Old and new observations, spanning more than a century, show that V154 has increased in period while V42 has decreased in period. V84, on the other hand, has shown large, erratic changes in period that do not appear to reflect the long term evolution of V84 through the HR diagram.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 40 publications
3
7
0
Order By: Relevance
“…4) for more than two hundred galactic Cepheids spread out over more than a century of observations. Similar observations of decreases and increases of periods for Cepheids of type II in M 13 and M 5 have been recently reported by Rabidoux et al (2010). As the models computed with CHeB cross the instability strip with a monotonous increase of the radius, the temporal derivative of the period is always positive.…”
Section: Discussionsupporting
confidence: 87%
“…4) for more than two hundred galactic Cepheids spread out over more than a century of observations. Similar observations of decreases and increases of periods for Cepheids of type II in M 13 and M 5 have been recently reported by Rabidoux et al (2010). As the models computed with CHeB cross the instability strip with a monotonous increase of the radius, the temporal derivative of the period is always positive.…”
Section: Discussionsupporting
confidence: 87%
“…The phase variation of M80-V1 suggests that it also experienced a significant period change during the 1970s (sometime between JD 2441000 and 2444000), and it has been pulsating with a longer period since then. These findings agree with previous studies: large and abrupt changes can often be observed in the periods of W Vir-type stars (Percy & Hoss 2000;Rabidoux et al 2010).…”
Section: Period Changessupporting
confidence: 94%
“…However, RVTs have been identified in the MCs (Soszyński et al 2008;Ripepi et al 2015). b) Alternating cycle behaviour -There is evidence of an interaction between the central star and the circumstellar envelope possibly causing the alternating cycle behaviour (Feast et al 2008;Rabidoux et al 2010). The final crossing of the instability strip before approaching the WD cooling sequence either for PEAGB or for TPAGB models appears a very plausible explanation.…”
Section: Pulsation and Evolutionary Implications For Type II Cepheidsmentioning
confidence: 99%